Modern Approaches to Learning Foreign Languages: Pendekatan Modern untuk Belajar Bahasa Asing - Nawaz, Sumaira; Azimovna, Abulova Zilola (Indonesian Journal of Education Methods Development, 2022)
The article provides detailed information on foreign language teaching methods. However, examples suitable for each method are given and analyzed. All types of methods are covered and their benefits are discussed.